Six new species of Nazeris Fauvel (Coleoptera, Staphylinidae, Paederinae) from Guangxi, South China - Hu, Jia-Yao; Li, Li-Zhen; Zhao, Mei-Jun (Zootaxa, 2012)
Six new species of Nazeris Fauvel collected from Dayao Mountain, Guangxi Province, are described and illustrated: N.dayaoensis Hu & Li, sp. n., N. luoi Hu & Li, sp. n., N. tani Hu & Li, sp. n., N. qini Hu & Li, sp. n., N. megalobus Hu &Li, sp. n. and N. grandis Hu & Li, sp. n. An identification key to the Nazeris species from Guangxi and its adjacent areas is provided.